A study of the parasitoid soft scale insect ( Exaeretopus tritici (Wil-liams)(Coccidae: Homoptera) infecting wheat( Choreia maculate) - Abdullah, Suaad Irdeny (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted on gregarious endoparasitic Choreia maculate (Order: Hymenoptera) which was parasites on the adult females of soft scale insects Exaeretopus tritici (Williams) which was attacked the wheat crop. The average percentage of the parasite and un parasite females reached 83.99 and 61.01 %, the adults had succeeded and they secreted a cotton egg sac and deposited a few number of eggs with an average of 11.2 egg and the average percentage of the hatching eggs was 8.6 % compared to parasite females, which normally deposited a large number of eggs with an average of 402.6 egg, The highest percentage of the hatching eggs was 83.8 % on the one hand، on the other hand، a large number of the un parasite females was 657 female which secreted a cotton egg sac and left their host plant toward the soil surface، searching for cracks or any shelter for eggs deposition in a cotton egg sac at soil depth ranged between (0-5) cm، with an average of 26 egg and the average percentage of the hatching eggs was 13 %, compared with the females which were found in the soil depth ranged between (20-25) cm with an average of 5 females. M-2 which deposited a few number of eggs reached 2 eggs. Female-1، the lowest percentage of egg hatching, reached 2%